2023
DOI: 10.1108/jcp-10-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Specialist courts and borderline personality disorder: a pilot study of the efficacy of the assessment and referral court list to reduce recidivist behaviour

Abstract: Purpose This paper aims to examine the ways in which the criminal justice system has evolved to accommodate mental illness. Mental health courts are one such alternative; these courts actively seek rehabilitative and therapeutic outcomes for participants. However, current literature suggests that these courts are ineffective for offenders who have been diagnosed with borderline personality disorder (BPD). Design/methodology/approach The aim of the current inquiry was to determine the degree to which particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…There has been a huge push in recent years within the CJS towards victim-oriented policy and procedures (Fielding 2013;Smith et al 2022). Yet, despite institutional agreement, there exists key divides within the general public's perceptions of victims (Lilley et al 2023b;Stevens et al 2024), defendants (Chesser et al 2023;Lewandowicz-Machnikowska et al 2023), and the appropriate treatment of both (Jones et al 2023;Sowersby et al 2022;Williams et al 2023). The current research, in line with previous findings, found that the British public demonstrates victim-oriented attitudes, as a higher proportion of respondents rated the court's ability to help victims as poor than rated the protection of the accused as poor (Kaukinen and Colavecchia 1999).…”
Section: Perceptions Of Victim Treatmentmentioning
confidence: 99%
“…There has been a huge push in recent years within the CJS towards victim-oriented policy and procedures (Fielding 2013;Smith et al 2022). Yet, despite institutional agreement, there exists key divides within the general public's perceptions of victims (Lilley et al 2023b;Stevens et al 2024), defendants (Chesser et al 2023;Lewandowicz-Machnikowska et al 2023), and the appropriate treatment of both (Jones et al 2023;Sowersby et al 2022;Williams et al 2023). The current research, in line with previous findings, found that the British public demonstrates victim-oriented attitudes, as a higher proportion of respondents rated the court's ability to help victims as poor than rated the protection of the accused as poor (Kaukinen and Colavecchia 1999).…”
Section: Perceptions Of Victim Treatmentmentioning
confidence: 99%
“…Treatment interventions, including therapy, are not fully used by the judiciary (Long et al, 2018), although they constitute important inhibitors of the demoralization process (Butler and Ledwith, 2021). The selection of an appropriate measure by the court to apply toward the juvenile is supposed to have the function of reducing the rate of relapse into antisocial behaviors (Chesser et al, 2023). There is a negligible number of reports of the effectiveness of correctional or treatment interventions in a group of juveniles remaining in isolation until the age of 21, who may constitute an important source of information on whether resocialization changes in their functioning have occurred (Hughes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%